Rural and Urban Differences in Children's Medicaid and CHIP Participation - Jennifer King; George M. Holmes; Rebecca T. Slifkin (SAGE Publishing, 2010)
Efforts to increase enrollment in Medicaid and the Children's Health Insurance Program (CHIP) among uninsured children would benefit from an understanding of how program participation varies in rural and urban areas. Using Current Population Survey data from the period 2006-2007, rural participation rates were slightly higher than urban rates in the nation overall. There was no rural-urban difference when comparisons were based on within-state variation, independent of adjustment for individual characteristics. For researchers examining health policy issues strongly influenced by state policies or other state-level factors, this study highlights the challenges presented by national data sets with small or nonexistent samples from geographic areas within some states.